Late Pleistocene and Holocene Environmental Change on the Olympic Peninsula, Washington - Gavin, Daniel G.; Brubaker, Linda B. (Ecological Studies, Analysis and Synthesis, 2015)
Utilizing a paleoecological approach, this volume brings together decades of research on the modern natural environment of Washington State's Olympic Peninsula. This review of past research on paleoenvironmental change since the Late Pleistocene presents paleoecological records of changing forest composition and fire over the last 14,000 years. This volume, and its conclusions, draws extensively from Dr. Daniel Gavin and Dr. Linda Brubaker's study of five Olympic Peninsula pollen records. The Olympic Peninsula is an ideal setting for studying the responses of ecosystems to past climate change. Located just south of the maximum ice-sheet extent during the Last Glacial Maximum, there is abundant evidence that it functioned as a glacial refugium; 29 taxa endemic to the peninsula likely persisted in such refugia. Furthermore, its uniquely steep rainfall gradient produces a wide range of habitats over short distances. A literature review, synthesis of published data, and close examination of the authors' investigations of post-glacial climate and vegetation change, this book features detailed color maps and data graphics.